Theoretical simulation of the photoassociation process for NaCs - 张常哲 郑斌 王军 孟庆田 (Chinese physics B, 2013)
We investigate the two-step association process of NaCs using the time-dependent wave packet method.Ground state atoms can be photoassociated to the low vibrational levels of the ground state for an NaCs molecule by the two-step association.The time-dependent Schro¨dinger equation of the association process is solved within a three-state model and the wave packet is propagated with the ＂split operator-Fourier transform＂ scheme and the rotating-wave approximation（RWA）.The vibrational population distribution of the ground state can be obtained by projecting the wave packet to every vibrational level of the ground state.The results not only show that for NaCs achievement of photoassociation production is accompanied by the photodissociation of the higher vibrational molecules,but also show that the vibrational distribution in lower vibrational levels of the ground state changes with the laser parameters.